Acceptance of Commercial Cricket Cultivation Technology in Nong Khai Province, Thailand - Panyasit, Kamoltip; Singhavara, Montri; Sakkarin, Nonthapot (International Journal of Innovative Research and Scientific Studies, 2022)
Nong Khai Province, Thailand is one of the provinces in the northeastern region that has been promoting a career known as the “Nong Khai Model Project” of cricket cultivation. This study aimed to research the factors affecting the acceptance of commercial cricket cultivation technology in Nong Khai Province, Thailand. The samples in this study included 500 farmers. The agricultural technology was cricket cultivation from the Nong Khai Model project that improved the mindset and way of cultivation, which was arranged by Khon Kaen University, Nong Khai Campus. The analyses, by the ordered logit and ordered probit models, were estimated with the maximum likelihood and marginal effects. The two models demonstrated non-different results. However, the factors were gender, age, cultivation experience, education, labor, monthly household income and agricultural information channel via academic journals or documents. These affected the acceptance with statistical significance. Therefore, the Department of Agricultural Extension and Department of Agriculture should publish information about cricket cultivation by focusing on the benefits of the operation or provide simple instructions.